Kajian Teori Breaking Bad Habit Sebagai Solusi Memutus Kebiasaan NegatifSiswa Dalam Pembelajaran - Teguh Hadi Wibowo (STIT Muhammadiyah Paciran Lamongan, 2020)
Abstract:This article was an assessment of breaking badhabits theory offered by E.R. Guthrie by providing reinforcement from an Islamic teaching point of view so that it could be used as a solution to break bad habits of students in a lesson. There are three methods offered by E.R. Guthrie in breaking bad habits: First, the threshold method. This method is in accordance with the four stages of break the habit of drinking khamrfound in Qur'an. Second, the fatigue method. This method is in accordance with the command to be patient in telling family members to pray as stated in Thāhā verse 132. Third, the incompatible response method. This method is in accordance with Islamic views, one of which is found in surah al-Burûj verses 10-11. In addition to the above three methods, in the view of Islam, there areelementsin a lesson that are no less important, namely the environmental elements, that good or bad the character of an individual canbe formed by the surrounding environment, as implied in the hadith of the Prophet Mohamed about the parable of a good friend such as musk oil traders and bad friends such as the blacksmith's fire blower.